A novel approach to intraoperative diagnosis of primary pigmented nodular adrenocortical disease - Nethrani Sameera Wijesekara Pathirana; Hasitha Udayakumara; A S K Banagala; M R Sumanatilleke; A V T Damayanthi; S R Constantine; G W Katulanda; Z T M Thowfeek; T Sasikanth; S Pathmanathan (Endocrinology, Diabetes & Metabolism Case Reports)
Cushing syndrome (CS) is an endocrine disorder with far-reaching complications that extend beyond the disease remission. Diagnosis of the aetiology of CS can be challenging, whether it is dependent or independent of adrenocorticotrophic hormone (ACTH). Here, we describe a case of ACTH-independent CS due to primary pigmented nodular adrenocortical disease (PPNAD) in a 33-year-old female patient with several complications of CS, including diabetes, hypertension, osteoporosis and severe depression with suicidal ideation. In this case, following the demonstration of ACTH independence of CS, it was challenging to localise the lesion as there were bilateral adrenal lesions. Furthermore, preoperative efforts in localisation in the form of adrenal venous sampling (AVS) failed. However, the diagnosis of PPNAD was confirmed using an intraoperative frozen section and macroscopy, and the patient underwent bilateral adrenalectomy during the same surgery. This case highlights a novel approach to diagnosing and managing PPNAD intraoperatively in a resource-limited setting where preoperative localisation studies have failed.